Assessing smartphone-derived heart rate variability as an indicator of general and oral health: an exploratory study - Guzzoni, Luiz Felipe Manosso; Soto, Vanessa Carvajal; Pereira, Victoria Lais; de Lima, Michele; dos Santos, Fábio André; Bortoluzzi, Marcelo Carlos (Journal of Oral Diagnosis, 2024)
Objective: This study aimed to investigate the feasibility and effectiveness of using smartphone-derived heart rate variability (HRV) as a diagnostic tool for assessing both general and oral health conditions. Methods: An exploratory and cross-sectional study was conducted. HRV was recorded through smartphone photoplethysmography (PPG). Were searched associations between HRV and the American Society of Anesthesiologists (ASA) risk classification in dentistry, tooth loss (TL), dental maintenance and rehabilitation status (DMRS), and periodontal disease (PD). To confirm the reliability of signal acquisition pattern by PPG method via smartphone, heart rate (HR) was compared using four additional devices. Results: The HR derived from the smartphone demonstrated reliability comparable to traditional monitoring devices. Significant associations were found between higher HRV scores with better oral health outcomes. Smartphone-derived HRV was able to detect comorbidity with 68.3% of sensitivity and 61.5% of specificity. Conclusion: This study underscores the potential of smartphone-derived HRV as a complementary diagnostic tool for evaluating both general and oral health conditions. The findings reveal discernible associations between HRV and the ASA classification for risk in dentistry and with the studied oral health parameters. HR derived from smartphone is reliable when compared with traditional cardiac monitoring devices.